When are impending retirees inspired to save: The role of agreeableness and future clarity - Simon A Moss; Era Ghafoori (Journal of Financial Therapy, 2020)
In the decade or so before they retire, many individuals do not save enough money to maintain their lifestyle after retirement. According to the self-continuity hypothesis, as individuals approach a transition in their life, such as retirement, they are not as willing to sacrifice pleasure now to benefit their future, impeding their tendency to save money judiciously and to manage their finances prudently. This longitudinal study, however, tested the hypothesis that impending retirees who are agreeable or perceive their future as vivid and certain, called future clarity, are more likely to manage their finances prudently, despite this looming transition. In particular, people who are agreeable tend to perceive their identity as more stable because the extent to which they value harmonious relationships does not abruptly escalate as retirement approaches. People who report future clarity tend to perceive the future as closer in time and, therefore, are more willing to sacrifice their pleasure to benefit this future. To assess these hypotheses, 597 impending retirees completed the same questionnaire twice, in consecutive years, to gauge their tendency to manage their finances prudently, called financial control, as well as their agreeableness and future clarity. As hypothesized, financial control tended to subside over time, but agreeableness and future clarity diminished this decline. As these findings imply, if impending retirees are exposed to opportunities they could pursue after they retire—clarifying their future goals and pursuits—they are likely to manage their finances more judiciously now.
Keywords: agreeableness; future clarity; retirees; savings